Derivational Suffixes in Animated Movie Dialogue: A Morphological Study of “Wish” (2023) - Surati Wagut, Anastasia Afri (Modality Journal: International Journal of Linguistics and Literature, 2025)
This study investigates derivational suffixes found in the animated film Wish (2023) produced by Walt Disney Animation Studios. The research focuses on identifying and analyzing the types and morphological processes of derivational suffixes as reflected in the film’s dialogue. Data were collected by transcribing the film script and analyzed using a qualitative descriptive method based on the frameworks of Katamba (1993, 1994) and McCarthy (2002). The study identified 30 instances of derivational suffixes, classified into six major types: Noun Derived from Verb (0,23%), Adjective Derived from Verb (0,06%), Adjective Derived from Noun (0,2%), Noun Derived from Adjective (0,1%), Adverb Derived from Adjective (0,33%), and Noun Derived from Noun (0,06%). The most frequent category was Adverb Derived from Adjective, while the least frequent were Noun Derived from Noun and Noun Derived from Adjective. The findings reveal that in popular media contexts, even suffixes with limited morphological variations such as-lycan appear frequently. This study contributes to morphological research by demonstrating how derivational processes operate in naturally occurring, conversational English. The results have implications for linguistic pedagogy, media discourse analysis, and understanding word formation in popular culture